Keabsahan Badal Haji pada Mubaddil yang Belum Pernah Melaksanakan Haji (Studi Komparatif Mazhab Maliki dan Syafii) - Jahada Mangka; Muhamad Saddam Nurdin; Nurfaikah Nasrulla (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2024)
This research seeks to ascertain the perspectives of the Maliki school and the Syafii school of thought on the validity of the badal hajj for individuals who have never performed the hajj.This research employs a qualitative methodology, utilizing comparative, normative, and conceptual approaches. The research findings revealed the following: firstly, the Maliki school of thought permits the implementation of the badal hajj for mubaddils who have never performed the hajj, and maintains that the hajj remains valid for the individual being replaced, despite some of their followers judging him as makruh. While Shafii school of thought, on the other hand, forbids the execution of the badal hajj on individuals who have never performed the hajj and declares the hajj invalid for the individual replacing them, as this action automatically transforms the hajj into a hajj Second, the similarities between the views of the Maliki school and the Shafii school of thought lie in their use of hadiths from 'Ibn 'Abbas, attributed to the Prophet PBUH. As for the differences, the Maliki school of thought uses general postulates, while the Shafii school of thought uses specific postulates regarding the badal hajj. After reading and studying, researchers are more likely to adopt the Shafii school's perspective due to their use of unique propositions for this particular problem. In the hadith, Rasulullah observed that he commanded a mubaddil to perform his own hajj before substituting it for someone else's. According to the ulama, the opinion of the Shafii school of thought is clear.